GAMBARAN PEMANFAATAN BUKU KESEHATAN IBU DAN ANAK (KIA) OLEH IBU HAMIL DALAM PERSIAPAN PERSALINAN DI DESA LATDALAM SAUMLAKI - Arvicha Fauziah; Kasmiati, Kasmiati; Kristiova Masnita Saragih; Jakob L. Jambormias (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
One of the preparations for childbirth is preparing a Maternal and Child Health Book (KIA) document. However, many pregnant women still do not have and do not use the KIA book. The results of the 2023 SDKI showed that 13.8% had owned and 5% had never owned a KIA book. The KIA book contains health information for mothers from pregnancy, childbirth, postpartum, and continues to record the health of newborns until the age of 6 years. The aim was to determine the overview of the use of the KIA book by pregnant women in preparing for childbirth in Latdalam Village, Tanimbar Islands Regency. The research method was quantitative with a descriptive research design. The activity was carried out in Latdalam Village in February 2024. The sample taken was a total population of 23 pregnant women. The instrument used a questionnaire. Data analysis used univariate analysis. The results showed that 95.65% of pregnant women did not have a KIA book, 100% of pregnant women did not use the KIA book in preparing for childbirth, and there was an increase in knowledge of 43.48% after being provided with counseling. Optimizing the use of the KIA book by pregnant women in preparing for childbirth is very effective.